Analysis of Implementation of Content Mastery Services in Overcoming Problems of Student Learning Difficulties (Systematic Literature Review Method) - Haura Hazima; Khairuddin (Journal for Lesson and Learning Studies, 2023)
Learning activities for every student only sometimes take place normally. It has an impact on students who have difficulty in learning. This study aims to analyze content mastery services in overcoming student learning difficulties. This type of research is Systematic Literature Review (SLR). Data sources as subjects and objects come from indexed journal literature with an electronic ISSN (International Standard Serial Number) published via the internet with the E-ISSN code. Data collection is done by surfing the internet from Google Scholar. The results of the study state that the results of the Systematic Literature Review of all research published in journals published from 2013 to 2022 confirm that several schools need to be more optimal in implementing content mastery services. The causes of the low implementation of content mastery services are several schools that have never implemented content mastery services, the absence of professional teachers in the field of guidance and counseling, and the lack of facilities from schools to carry out content mastery services. The solutions to the low implementation of content mastery services in overcoming student learning difficulties include schools providing facilities to supervise teachers to carry out content mastery services and improving the quality of services in guidance and counseling.